Biogas Production From Cassava Starch Effluent Using Microalgae As Biostabilisator - B. Budiyono; Tutuk Djoko Kusworo (International Journal of Science and Engineering, 2011)
The rapid growing of Indonesian population is emerging several critical national issues i.e. energy, food, environmental, water, transportation, as well as law and human right. As an agricultural country, Indonesia has abundant of biomass wastes such as agricultural wastes include the cassava starch wastes. The problem is that the effluent from cassava starch factories is released directly into the river before properly treatment. It has been a great source of pollution and has caused environmental problems to the nearby rural population. The possible alternative to solve the problem is by converting waste to energy biogas in the biodigester. The main problem of the biogas production of cassava starch effluent is acid forming-bacteria quickly produced acid resulting significantly in declining pH below the neutral pH and diminishing growth of methane bacteria. Hence, the only one of the method to cover this problem is by adding microalgae as biostabilisator of pH. Microalgae can also be used as purifier agent to absorb CO2.The general objective of this research project was to develop an integrated process of biogas production and purification from cassava starch effluent by using biostabilisator agent microalgae. This study has been focused on the used of urea, ruminant, yeast, microalgae, the treatment of gelled and ungelled feed for biogas production, pH control during biogas production using buffer Na2CO3, and feeding management in the semi-continuous process of biogas production. The result can be concluded as follows: i) The biogas production increased after cassava starch effluent and yeast was added, ii) Biogas production with microalgae and cassava starch effluent, yeast, ruminant bacteria, and urea were 726.43 ml/g total solid, iii) Biogas production without  microalgae was 189 ml/g total solid.